Prevalence of methicillin-resistant Staphylococcus aureus and pattern of antimicrobial resistance in mastitis milk of cattle in Chitwan, Nepal - Asmita Shrestha; Rebanta Kumar Bhattarai; Himal Luitel; Surendra Karki; Hom Bahadur Basnet (BMC Veterinary Research, 2021)
Abstract Background The threat of methicillin-resistant Staphylococcus aureus (MRSA) exists globally and has been listed as a priority pathogen by the World Health Organization. One of the sources of MRSA emergence is livestock and its products, often raised in poor husbandry conditions. There are limited studies in Nepal to understand the prevalence of MRSA in dairy animals and its antimicrobial resistance (AMR) profile. A cross-sectional study was conducted in Chitwan, one of the major milk-producing districts of Nepal, from February 2018 to September 2019 to estimate the prevalence of MRSA in milk samples and its AMR profile. The collected milk samples (n = 460) were screened using the California Mastitis Test (CMT) and positive samples were subjected to microbiological analysis to isolate and identify S. aureus. Polymerase Chain Reaction (PCR) was used to identify the presence of the mecA gene and screen for MRSA. Results In total, 41.5% (191/460) of milk samples were positive in the CMT test. Out of 191 CMT positive milk samples, the biochemical tests showed that the prevalence of S. aureus was 15.2% (29/191). Among the 29 S. aureus isolates, 6.9% (2/29) were identified as MRSA based on the detection of a mecA gene. This indicates that that 1.05% (2/191) of mastitis milk samples had MRSA. The antibiotic sensitivity test showed that 75.9% (22/29) and 48.3% (14/29) S. aureus isolates were found to be sensitive to Cefazolin and Tetracycline respectively (48.3%), whereas 100% of the isolates were resistant to Ampicillin. In total 96.6% (28/29) of S. aureus isolates were multidrug-resistant (MDR). Conclusions This study revealed a high prevalence of S. aureus-mediated subclinical mastitis in dairy herds in Chitwan, Nepal, with a small proportion of it being MRSA carrying a mecA gene. This S. aureus, CoNS, and MRSA contaminated milk poses a public health risk due to the presence of a phenotype that is resistant to very commonly used antibiotics. It is suggested that dairy herds be screened for subclinical mastitis and treatments for the animals be based on antibiotic susceptibility tests to reduce the prevalence of AMR. Furthermore, future studies should focus on the Staphylococcus spp. to explore the antibiotic resistance genes in addition to the mecA gene to ensure public health.